Aplikasi Michat Sebagai Media Prostitusi Online di Banjarmasin - Irma Damayanti; Yusuf Hidayat; Reski P (PAKIS (Publikasi Berkala Pendidikan Ilmu Sosial), 2022)
This study aims to (1) find out the pattern of online prostitution activities through the MiChat application (2) find out the competition in online prostitution through the MiChat application. This research used a qualitative research method. To obtain samples, this research used purposive sampling. Criteria for informants in this study were Commercial Sex Workers who worked online aged 20-35 years. The data collection was obtained by using observation and interview techniques with 3 (three) informants namely Mirna, Ayu and Nina and documentation. The data was analyzed by using data reduction, display and verification steps. The results showed that: (1) The pattern of online prostitution activities through the MiChat application was divided into two, namely working with pimps and independently. Commercial Sex Workers who collaborate with their pimps only serve guests their pimps are looking for. Whereas commercial sex workers who work independently must carry out their own promotions and negotiations. (2) Competition that occured in Online prostitution was that with fellow colleagues of the same profession, with fraudsters who take advantage and appearance in order to be able to maintain the existence of Commercial Sex Workers. Based on the results of this study, it is suggested to block internet sites that provide all matters relating to prostitution and pornography need to be controled by the government oversight and laws on internet sites and their uses even though there are laws to prostitution but a powerful way to overcome them is so that everyone fortifies themselves and their families by reinforcing morals with religious values and other values